2007
DOI: 10.1017/s0033291707001699
|View full text |Cite
|
Sign up to set email alerts
|

Social fears and social phobia in the USA: results from the National Comorbidity Survey Replication

Abstract: Background-Despite heightened awareness of the clinical significance of social phobia, information is still lacking about putative subtypes, functional impairment, and treatment-seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
469
4
31

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(572 citation statements)
references
References 68 publications
43
469
4
31
Order By: Relevance
“…Numerous clinical and non-clinical studies have revealed that SA is strongly associated with a smaller social network (Falk Dahl & Dahl, 2010). Moreover, SA individuals reported reduced social support (e.g., Ruscio et al, 2008), fewer friends, greater rates of living alone, and a significantly lower prevalence of club/association membership and activity (Falk Dahl & Dahl, 2010). In addition to smaller social networks, SA is associated with fewer close relationships, such as intimate friendships or romantic partnerships (e.g., Chou, Liang, & Sareen, 2011), and lower rates of marriage or marriage-like relationships (Falk Dahl & Dahl, 2010).…”
Section: Social Anxiety Loneliness and Subjective Well-beingmentioning
confidence: 99%
“…Numerous clinical and non-clinical studies have revealed that SA is strongly associated with a smaller social network (Falk Dahl & Dahl, 2010). Moreover, SA individuals reported reduced social support (e.g., Ruscio et al, 2008), fewer friends, greater rates of living alone, and a significantly lower prevalence of club/association membership and activity (Falk Dahl & Dahl, 2010). In addition to smaller social networks, SA is associated with fewer close relationships, such as intimate friendships or romantic partnerships (e.g., Chou, Liang, & Sareen, 2011), and lower rates of marriage or marriage-like relationships (Falk Dahl & Dahl, 2010).…”
Section: Social Anxiety Loneliness and Subjective Well-beingmentioning
confidence: 99%
“…Social phobia (SP) is one of the most common mental disorders in adults, adolescents and children with lifetime prevalence rates of up to 12,1% (Ruscio et al 2008). In the Diagnostic Statistical Manual of Mental Disorders (DSM-IV; American Psychiatric Association [APA], 1994), SP is defined as an excessive, irrational fear of social or performance situations due to the expectation that others will scrutinize the person's actions.…”
Section: Introductionmentioning
confidence: 99%
“…The one study that failed to find any evidence for content domains was based on a community sample rather than a social phobia sample. [14] . In addition to these factor analytic findings, the DSM-V committee recognized an emerging literature on fear of blushing and sweating.…”
mentioning
confidence: 99%